2017
DOI: 10.3389/fpsyg.2017.00522
|View full text |Cite
|
Sign up to set email alerts
|

The BEST Dataset of Language Proficiency

Abstract: http://journal.frontiersin.org/article/10.3389/fpsyg.2017.00522/full#supplementary-materialThis research has been partially funded by grants PSI2015-65689-P, PSI2015-67353-R, and SEV-2015-0490 from the Spanish Government, AThEME-613465 from the European Union and a personal fellowship given by the BBVA Foundation to the last author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 17 publications
0
92
0
Order By: Relevance
“…We only included participants with minimum score of 60% in English (80% for Spanish), which is equivalent to a minimum of a B2 level (C1 for Spanish) according to the Common European Framework of reference for languages 26 . Participants also completed a test of productive vocabulary (BEST picture naming task 28 ) and had a minimum score of 40 out of 65 for English (61 out of 65 for Spanish). Participants were asked to rate their English and Spanish levels overall on a 1-to-10 scale as well as their reading skills in that language.…”
Section: Methodsmentioning
confidence: 99%
“…We only included participants with minimum score of 60% in English (80% for Spanish), which is equivalent to a minimum of a B2 level (C1 for Spanish) according to the Common European Framework of reference for languages 26 . Participants also completed a test of productive vocabulary (BEST picture naming task 28 ) and had a minimum score of 40 out of 65 for English (61 out of 65 for Spanish). Participants were asked to rate their English and Spanish levels overall on a 1-to-10 scale as well as their reading skills in that language.…”
Section: Methodsmentioning
confidence: 99%
“…Spanish-Basque bilinguals had also acquired both languages before the age of 6, and they were also attending a bilingual school. We assessed language proficiency with three different measurements (see Table 1): a subjective scale, in which participants rated their language competence on a scale from 0 to 10; a 20-item adapted version of a picture naming task [21]; the LexTale (a lexical decision task, cf., for the English version [22]; for the Spanish version [23]; and for the Basque version [21]). In addition to measuring proficiency in Spanish, Basque, and Catalan (where relevant), we also made sure that, despite English being a mandatory subject in all Spanish schools, the participants’ English level was relatively low as assessed by the English LexTale (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Only participants who scored at least at the 75 th centile (more than 17 correct answers) on the test were included in the study and considered relatively skilled readers, and the two groups were matched according to the raw scores (deaf: mean=21.90, SD=3.08, range=18-27; hearing: mean=23.70, SD=3.25, range=17-27). All the participants also completed the Spanish version of LexTALE (Izura, Cuetos, & Brysbaert, 2014), a lexical decision test comprising 60 real words and 30 nonwords that provides a good estimate of language knowledge (e.g., de Bruin, Carreiras, & Duñabeitia, 2017;Lemhöfer & Broersma, 2012). The final scores (in percentages) showed that both groups completed the test accurately, demonstrating a high language knowledge and no differences among the groups (deaf: mean=91.16, SD=13.22;hearing: mean=95.66,SD=3.43;p=.22)…”
Section: Participantsmentioning
confidence: 99%